SEG Technical Program Expanded Abstracts 1982 1982
DOI: 10.1190/1.1826880
|View full text |Cite
|
Sign up to set email alerts
|

The signature of an air gun array: Computation from near‐field measurements including interactions—practical considerations

Abstract: We have refined our system for calculating the signa; ture of an interacting air gun array from near-field measurements of its pressure field. We use an iterative technique to calculate a notional array of noninteracting sources from the near-field hydrophone measurements The notional signatures form the basis for calculating the array signature in any direction. The success of our iterative technique depends upon prudent positioning of the hydrophones, one close to each air gun. In normal operation the forwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 2 publications
(5 reference statements)
0
28
0
Order By: Relevance
“…Theoretically, the far-field source signature can be estimated from near-field measurements [Ziolkowski et al, 1982;Parkes et al, 1984]. Each gun was equipped with a near-field hydrophone, but most of them ceased to work as soon as the guns were put in the water, which meant that it would be impossible to follow the procedure described by Ziolkowski [1987].…”
Section: Prestack Processingmentioning
confidence: 99%
“…Theoretically, the far-field source signature can be estimated from near-field measurements [Ziolkowski et al, 1982;Parkes et al, 1984]. Each gun was equipped with a near-field hydrophone, but most of them ceased to work as soon as the guns were put in the water, which meant that it would be impossible to follow the procedure described by Ziolkowski [1987].…”
Section: Prestack Processingmentioning
confidence: 99%
“…In such cases, clustered air guns are typically used (Dragoset, 1990). Ziolkowski et al (1982) and Parkes et al (1984) showed how the monopole source function (termed the 'notional source signature' by them) could be measured using a hydrophone placed about 1 m from the air gun bubble. The VSP source obtains its spectral flatness by using clusters rather than by using a large mix of volumes.…”
Section: Marine Sources: Air Gunsmentioning
confidence: 99%
“…Landr and Sollie (1992) constrained them to be solutions of the bubble equation of motion (described in the succeeding text); Amundsen (1993a) allowed them to be arbitrary functions. These two methods and that of Ziolkowski et al (1982) combined with Parkes et al (1984) were compared by Laws et al (1998) to measurements made with a farfield hydrophone, and the three methods were found to be of similar accuracy. Ziolkowski (1980) had proposed a method using 'scaled arrays,' but this involved doubling the shot interval and was not adopted.…”
Section: Marine Sources: Air Gunsmentioning
confidence: 99%
“…For each experiment, the near-field measurements were used to compute the notional signatures after the method described by Parkes, Ziolkowski, Hatton and Haugland (1984). From the notional signatures thus obtained, the field may be computed at any point in space; in particular, the far-field values are easily determined.…”
Section: Experimental Verijkation Of Energy-interaction By the Far-fimentioning
confidence: 99%